The First Jesuit in Vilnius: the Letters of Alfonso Salmerón to Ignatius of Loyola - Pociūtė, Dainora; Dugo, Carmen Caro Caro (Literatūra, 2008)
The publication focuses on the visit of the Spanish Jesuit Alfonso Salmerón (1515–1585) in Vilnius in the late 1555. The visit of the first Jesuit in Vilnius lasted one month from October the 28th to the end of November. It was the first visit of the member of the Society of Jesus in the Grand Duchy of Lithuania during which the possibilities to open the first Jesuit College in the region were tested. Salmerón came to Vilnius as the attendant of the Papal nuncio Aloisio Lippomano (1496–1559) who in the same year was delegated to the official nunciature to Poland and Lihuania. The details of Salmerón’s visit were discussed in the three surviving letters of Salmerón to his close friend Ingantius of Loyola (1491–1556), the founder and the Superior General of the Society of Jesus. Two of them were written before the arrival in Vilnius from Augsburg (September 1) and Warszaw (October 10), the third one was sent from Wien (on January the 1st, 1556) after the visit to the Capital of the Grand Duchy. Though in the first two letters the possibility of establishing the Jesuit College in Vilnius was expressed quite positively, the situation was changed after the visit to Vilnius and the conversation with the King of Poland and the Grand Duke of Lithuania SigismundusAugustus. In the third letter to Lojola, Salmerón rejected the possibility of opening the College because of the situation in the state where he noted very strong inclination of the local nobility to protestantism (“heresy”).The three Spanish letters of Salmerón to Loyola provide many other interesting details about the religious context of Poland and Lithuania in the middle of the 16th century and the Jesuit Counter-Reformation politics in the region.